A new dietary strategy for long-term treatment of the metabolic syndrome is compared with the American Heart Association (AHA) guidelines: the MEtabolic Syndrome REduction in NAvarra (RESMENA) project. Issue 4 (28th February 2014) - de la Iglesia, Rocio; Lopez-Legarrea, Patricia; Abete, Itziar; Bondia-Pons, Isabel; Navas-Carretero, Santiago; Forga, Luis; Martinez, J. Alfredo; Zulet, M. Angeles
<x content-type="archive" xml:space="preserve">Abstract</x> The long-term effects of dietary strategies designed to combat the metabolic syndrome (MetS) remain unknown. The present study evaluated the effectiveness of a new dietary strategy based on macronutrient distribution, antioxidant capacity and meal frequency (MEtabolic Syndrome REduction in NAvarra (RESMENA) diet) for the treatment of the MetS when compared with the American Heart Association guidelines, used as Control. Subjects with the MetS (fifty-two men and forty-one women, age 49 (se 1) years, BMI 36·11 (se 0·5) kg/m2) were randomly assigned to one of two dietary groups. After a 2-month nutritional-learning intervention period, during which a nutritional assessment was made for the participants every 15 d, a 4-month self-control period began. No significant differences were found between the groups concerning anthropometry, but only the RESMENA group exhibited a significant decrease in body weight ( − 1·7 %; P= 0·018), BMI ( − 1·7 %; P= 0·019), waist circumference ( − 1·8 %; P= 0·021), waist:hip ratio ( − 1·4 %; P= 0·035) and android fat mass ( − 6·9 %; P= 0·008). The RESMENA group exhibited a significant decrease in alanine aminotransferase and aspartate aminotransferase (AST) concentrations ( − 26·8 %; P= 0·008 and − 14·0 %; P= 0·018, respectively), while the Control group exhibited a significant increase in glucose (7·9 %; P= 0·011), AST (11·3 %; P= 0·045) and uric acid (9·0 %; P< 0·001) concentrations. LDL-cholesterol (LDL-C) concentrations were increased (Control group: 34·4 %; P< 0·001 and RESMENA group: 33·8 %; P< 0·001), but interestingly so were the LDL-C:apoB ratio (Control group: 28·7 %; P< 0·001, RESMENA group: 17·1 %; P= 0·009) and HDL-cholesterol concentrations (Control group: 21·1 %; P< 0·001, RESMENA group: 8·7; P= 0·001). Fibre was the dietary component that most contributed to the improvement of anthropometry, while body-weight loss explained changes in some biochemical markers. In conclusion, the RESMENA diet is a good long-term dietary treatment for the MetS.